The Chemical Composition Of The White Carrak Plant And Its Medicinal Role (Texas Journal of Medical Science, 2024)
White carrack is a medicinal plant that has been used in medicine since ancient times. The composition of white carrack is rich in various vitamins and microelements. It is rich in vitamins A, E, F, K and V. Its leaves, roots, and seeds are used to make oil and whey. Due to its antioxidant properties, silymarin helps restore liver tissue